The Effect of Capital Adequacy and Credit Risk on Profitability with Good Corporate Governance as Moderating Variable - Prameswari, Ida Ayu Nirma; Ratnadi, Ni Made Dwi; Gayatri,; Suaryana, I Gusti Ngurah Agung (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to obtain empirical evidence about the effect of capital adequacy and credit risk on profitability and examine the role of good corporate governance in moderating the effect of capital adequacy and credit risk on profitability. This study uses non-probability sampling methods and purposive sampling techniques. The data used are secondary data obtained from annual reports of banking companies listed on the Indonesia Stock Exchange and included in the Corporate Governance Perception Index assessment in the 2011-2019 period. Data analysis techniques using moderated regression analysis tests. The results of the analysis show that capital adequacy has a positive effect on profitability, credit risk has a negative effect on profitability, good corporate governance has no effect on profitability.